2021
DOI: 10.3389/fcvm.2021.714774
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Adaptation of the Cardiomyocyte to Chronic Mitral Regurgitation

Abstract: Introduction: Mitral regurgitation (MR) imposes volume overload on the left ventricle (LV) and elevates wall stress, triggering its adverse remodeling. Pronounced LV dilation, minimal wall thinning, and a gradual decline in cardiac ejection fraction (EF) are observed. The structural changes in the myocardium that define these gross, organ level remodeling are not known. Cardiomyocyte elongation and slippage have both been hypothesized, but neither are confirmed, nor are the changes to the cardiomyocyte structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
3
5
0
Order By: Relevance
“…In addition, MR causes a loss of the linearity of the mitochondria along the sarcomeres, clustering around the nucleus and sarcomeres, and abnormalities in the cristae. Studies have reported that these structural changes are associated with mitochondrial dysfunction [ 31 ] and may contribute to the development of oxidative stress [ 38 , 40 , 41 ], which supports our findings of mitochondrial quality degradation in MR. Furthermore, in the current manuscript, we demonstrated the presence of vacuoles in the heart of MR rats more than in the heart of treatment groups or sham rats.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, MR causes a loss of the linearity of the mitochondria along the sarcomeres, clustering around the nucleus and sarcomeres, and abnormalities in the cristae. Studies have reported that these structural changes are associated with mitochondrial dysfunction [ 31 ] and may contribute to the development of oxidative stress [ 38 , 40 , 41 ], which supports our findings of mitochondrial quality degradation in MR. Furthermore, in the current manuscript, we demonstrated the presence of vacuoles in the heart of MR rats more than in the heart of treatment groups or sham rats.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we also explored ultrastructural changes and measured sarcomeric length in the myocytes of a rodent model of MR. In MR rats, a reduction in sarcomeric length was observed in this study similar to previous reports [ 38 , 39 ], which could be due to the breakdown of structural organization, especially the thin filament [ 38 ]. In addition, MR causes a loss of the linearity of the mitochondria along the sarcomeres, clustering around the nucleus and sarcomeres, and abnormalities in the cristae.…”
Section: Discussionsupporting
confidence: 91%
“…Chronic mitral regurgitation (after 2, 10, and 20 weeks), confirmed by Doppler measurements, resulted in LV dilatation and maladaptive cardiomyocyte changes but did not result in HFrEF. 105 A closed-chest approach was presented recently via inserting a needle through the xiphoidal cartilage and the apex to perforate the mitral valve leaflet under echocardiography guidance. 106 Besides the advantages of less invasive techniques, use of these approaches may increase with improved imaging devices.…”
Section: Small Animal Models Of Volume Overloadmentioning
confidence: 99%
“…A drop in ejection fraction is noticed at 14 weeks with myocyte and extracellular matrix remodeling and a transcriptomic shift illustrating upregulation of oxidative stress pathways [ 92 ]. Cardiomyocyte elongation, cytoskeletal disorganization, and loss of mitochondrial networking represent the ultrastructural bases of this remodeling [ 93 ]. The low-pressure volume overloaded mitral regurgitation model can be combined with the LAD ligation-based ischemic model to better reproduce the chronic ischemic DCM profile [ 94 ].…”
Section: Volume Overload Modelsmentioning
confidence: 99%